Mastering Advanced Rhinoplasty - Gubisch, Wolfgang (Springer International Publishing, 2018)
This clearly structured and beautifully illustrated atlas, which includes numerous high-quality pre-, intra-, and postoperative pictures, documents the techniques employed in order to deal with the problems typically encountered following a previous failed rhinoplasty. Each chapter also contains a description of the authors' standard procedure for treating the problem in question and describes the precautions to be taken in order to avoid similar failures. The techniques covered include extracorporeal and total septal reconstruction, reconstruction of the over resected tip, the sliding technique for reduction of the over projected tip, the use of alloplastic fascia or alternatively free diced cartilage for camouflaging or volume augmentation, and saddle nose correction. Mastering Advanced Rhinoplasty will be of value to both novice and experienced practitioners seeking to achieve the best results for patients who frequently present with challenging problems.